STATE MANAGEMENT OF THE PROCESSES OF DEVELOPING AN INCLUSIVE AND BARRIER-FREE ENVIRONMENT (Coordinates of Public Administration, 2026)
The article examines the peculiarities of public administration in the processes of developing an inclusive and barrier-free environment in Ukraine under the conditions of contemporary social transformations, digitalization, and European integration processes. The regulatory, legal, and organizational foundations of state policy formation in the field of ensuring equal access of citizens to public services, infrastructure, education, employment, and digital resources are analyzed. It is determined that public administration of the processes of developing an inclusive and barrier-free environment is implemented through six key dimensions: physical, informational, digital, social and civic, economic, and educational. The physical dimension involves ensuring architectural accessibility of buildings, public transport, and urban infrastructure for people with reduced mobility. The informational dimension is aimed at ensuring accessible communication through the use of sign language interpretation, Braille, and plain language. The digital dimension covers the adaptation of governmental web resources and electronic public services to the needs of persons with visual, hearing, or motor impairments. The social and civic dimension focuses on creating conditions for equal participation of all citizens in political, cultural, and social life. The economic dimension provides for the promotion of employment opportunities for persons with disabilities and veterans, as well as the adaptation of workplaces in accordance with the principles of inclusiveness. The educational dimension defines the transition from institutionalized upbringing to comprehensive inclusive education at all educational levels. The article substantiates the necessity of improving public administration mechanisms, interagency cooperation, strategic planning, and monitoring of the effectiveness of state policy implementation in the field of barrier-free accessibility. It is concluded that the development of an inclusive and barrier-free environment is an important prerequisite for ensuring social justice, protecting human rights, improving the quality of life of the population, and achieving sustainable state development.